'Débrouillez-Vous': Women's Work, Transactional Sex, and the Politics of Social Networks. Issue 1 (1st January 2018) - Braun, Lesley Nicole
ABSTRACT: Women in Kinshasa, Democratic Republic of Congo are increasingly entering new professions partly due to an increase in higher education levels. In so doing, and as they become more visible in political and economic spheres, women are subjected to new forms of moral suspicion. While women have historically maintained a strong presence in the informal sector, such as commerce, new urban modes of employment dictate new kinds of visibility. It is within this context that notions of femininity and female virtue in Kinshasa continue to be redefined. This article explores several modes of employment for women, such as money-changing, journalism, and politics as they relate to local concepts of encadrement (supervision) and débrouillardisme (resourcefulness). Further, it also examines the threat that a woman's social network outside of her kin poses to men, as well as how women's participation in the economic sphere can motivate distrust between the genders.